2009
DOI: 10.1021/je900224w
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Adsorption Measurements of Pure Nitrogen, Carbon Dioxide, and Methane on a Carbon Molecular Sieve at Cryogenic Temperatures and High Pressures

Abstract: A detailed experimental study of the adsorption behavior at equilibrium of pure nitrogen, methane, and carbon dioxide gases on a commercial carbon molecular sieve (Shirasagi MSC 3K-161) is reported at temperatures between 115 K to 323 K and pressures up to 5 MPa. A volumetric-type apparatus was used to obtain over 200 excess (Gibbs) adsorption capacity data over this range of pressure and temperature with an estimated uncertainty of 4 %. The absolute adsorption isotherms were type I in the IUPAC classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…A schematic of the custom built volumetric adsorption apparatus is shown in Figure 1. The construction and operation of this apparatus is described in detail elsewhere [12][13][14] . Here, we provide a brief description of the key features of this apparatus, the procedures followed to calibrate its internal volumes, and the experimental workflow used to measure helium adsorption.…”
Section: High-pressure Volumetric Adsorption Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic of the custom built volumetric adsorption apparatus is shown in Figure 1. The construction and operation of this apparatus is described in detail elsewhere [12][13][14] . Here, we provide a brief description of the key features of this apparatus, the procedures followed to calibrate its internal volumes, and the experimental workflow used to measure helium adsorption.…”
Section: High-pressure Volumetric Adsorption Apparatusmentioning
confidence: 99%
“…Watson et al 12 showed that the dilation of the adsorption and loading cells with pressure contributes a negligible uncertainty to the volume of either cell.…”
Section: High-pressure Volumetric Adsorption Apparatusmentioning
confidence: 99%
“…Zhou et al [54] measured CH 4 adsorption on activated carbon AX-21 in a wide temperature range from 233 to 333 K and up to 10 MPa. Watson et al [55] measured the adsorption of pure CH 4 , N 2 and CO 2 on a carbon molecular sieve MSC 3K-161 at temperatures from 115 to 323 K and up to 5 MPa. Meanwhile, Savitz et al [56] measured the adsorption isotherms of CH 4 , C 2 H 6 and C 3 H 8 on highsilica zeolites.…”
Section: Available Experimental Data Of Gas Adsorption On Carbons Andmentioning
confidence: 99%
“…Over the years, many researchers have studied pure and binary adsorption of carbon dioxide and methane on different commercial adsorbents, such as zeolite 13X [6], activated carbon [7], carbon molecular sieve [8], ZSM-5 [9], and synthesized adsorbents such as zeolite T [10] and zeolite β [2].…”
Section: Introductionmentioning
confidence: 99%